Pengaruh profitabilitas likuiditas dan kebijakan dividen terhadap harga saham perusahaan perbankan yang terdaftar di bursa efek indonesia - Ariko Beni (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2023)
This research aims to determine the influence of return of asset (ROA), cash ratio(CR), and dividend payout ratio (DPR) variables on the stock price (HS) variable at the company banking which is listed in the Indonesia Stock Exchange (BEI) with 3-yearsresearch period in 2019-2021. The population used in this research is 46 banking companys which is listed in Indonesia Stock Exchange (BEI). The Sampling technique used purposive sampling. Pursuant to technique of taking purposive sampling data obtained sample of 12 firms banking which is listed in Indonesia stock Exchange (BEI). The data in the research used in the form of secondary data are financial statements of banking companies which is listed in Indonesia Stock Exchange (BEI) and processed with using SPSS(Statistical Product and Service Solution) software. The results showed that the return onassets (ROA) positive and significant to the stock prices, cash ratio (CR) negative and not significant to the stock prices, dividend payout ratio (DPR) positive and significant to thestock prices.